Reaction pathway and kinetic modeling for transformation of light olefins over SAPO-34 in the absence of methanol. (15th March 2022) - Zhang, Yu-Ling; Li, Xue-Gang; Xiao, Wen-De
Graphical abstract: Highlights: SAPO-34 catalyzed olefins cracking well obeys oligomerization-cracking mechanism. Direct transformation between propene and butene dominates when fed separately. Cracking rates of C3 –C4 olefins over SAPO-34 are close to those over ZSM-5. Cracking rates of C5 –C6 olefins over SAPO-34 are far lower than those over ZSM-5. SAPO-34 promotes higher propene yield than ZSM-5 does in C4+ olefins cracking. Abstract: The current studies on SAPO-34 catalyzed MTO process are generally based on the hydrocarbon-pool mechanism, in which the individual olefin is generated in parallel by the competing reactions without interconversion of the resulted olefins. This situation is surely oversimplified and makes the reaction mechanism confusing. In this work, we investigated C3 –C6 olefins transformation over SAPO-34 without methanol co-feeding to examine whether the oligomerization-cracking mechanism is applicable. Conversion pathways for individual olefin were discriminated with dimer-, trimer-, even tetramerization, by using Delplot analysis. The final reaction network was constructed with 11 reactions and a satisfactory correlation was achieved. Further validation tests were carried out by feeding C4 and C5 olefins mixture with excellent prediction performance obtained for the main product distribution, and comparison between SAPO-34 and ZSM-5 was done for a C4+ olefin feeding case, showing that SAPO-34 was much superior to ZSM-5 for higher olefin cracking.